Prevalence of severe asthma among adults and adolescents in Tanta, Egypt - Moustafa Kamel Shams Eldin; Amira Abdelgalil Elkholy; Mohamed Basiony Hamza; Radwa Mahmoud El Sharaby; Ayman Abdel Hamid Farghaly; Heba Ahmed Salem; Mohamed Samir Khedr; Amgad Abd El Raouf Farhat (The Egyptian Journal of Bronchology)
Abstract Background Severe asthma is defined by challenges in attaining control, even with aggressive treatment. Understanding the prevalence of severe refractory asthma in contrast to severe asthma with concomitant modifiable factors is crucial for informed clinical decision-making. Aim To assess severe refractory asthma prevalence among adults and adolescent’s asthmatic patients in Tanta, Egypt, and evaluate the level of different biomarkers including fractional exhaled nitric oxide (FeNO), total serum IgE, blood, and sputum eosinophils among those patients. Methods This prospective observational cross-sectional study included 1443 patients, consisting of 1115 adults (aged over 19 years) and 328 adolescents (aged 11–19 years), who had been diagnosed with asthma based on the GINA 2024 criteria. Results Occupational exposure and co-morbidities in adults were significantly higher in severe asthma with concomitant modifiable factors group as compared to mild, moderate, and severe refractory asthma groups. There was a significant positive correlation between (FeNO, total serum IgE, blood, and sputum eosinophils). FeNO, total serum IgE, and blood eosinophil count and sputum eosinophils percentage showed significant increase in severe refractory asthma as compared to severe asthma with concomitant modifiable factors group in both adults (p = 0.001 for all) and adolescents (p = 0.001, 0.007, 0.007, 0.006 respectively). Conclusions There was overlap group between severe refractory asthma and severe asthma with concomitant modifiable factors group defined as patients being adherent to medications and displaying correct inhaler technique but had ongoing exposure and unmanaged comorbidities with high inflammatory biomarkers. The prevalence of severe refractory asthma in adults and adolescents among asthmatic patients in Tanta, Egypt, was (6.5%) in adults and (2.4%) in adolescents. After adding overlap group to severe refractory asthma group, prevalence of severe refractory asthma increased to become (10.5%) in adults and (4.3%) in adolescents. FeNO is a noninvasive and easily performable objective biomarker of airway inflammation.